Pollination syndrome and breeding system of four reforestation tree species in Mt. Makiling, Luzon, Philippines - Escobin, Ramiro P.; Payawal, Pacifico C.; Cervancia, Cleofas R. (2004)
The pollination syndrome and breeding system of four reforestation tree species in Mt. Makiling, Laguna Province in Southern Luzon, Philippines, namely; Acacia auriculiformis Cunn. ex Benth. (auri), Vitex parviflora Juss. (molave), Leucaena leucocephala (Lam.) de Wlt (ipil-ipil, El Salvador Strain) and Pterocarpus indicus Willd.1 (narra) were investigated. Floral buds were enclosed with pollination bags and nets to exclude insect visitors/ pollinators of each species, with a corresponding number of buds tagged and left open to serve as control. The inflorescence of L. leucocephala was enclosed with paper packets to exclude floral visitors and wind-borne pollen grains. Results of the pollination bag experiments suggested that A. auriculiformis, V. parviflora and P. indicus were out crossing and entomophilous. Important pollinators of the species were medium- to large-sized bees. Floral morphology exhibited the bee floral syndrome. leucaena leucocephala is self-compatible and shows floral characteristics for anemophily. The rest of the species studied is self-incompatible and dichogamous.
Keywords: Pollination by insects; Reforestation -- Mount Makiling (Laguna); Mount Makiling (Laguna) -- Conservation; Plant breeding